2018
DOI: 10.1213/ane.0000000000002242
|View full text |Cite
|
Sign up to set email alerts
|

Inciting Events Associated With Lumbar Facet Joint Pain

Abstract: Inciting events are common in patients diagnosed with lumbar facetogenic pain and may be associated with a positive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The results for response to RFA among age, BMI, gender, and smoking correlate with those of other studies that examined outcomes at 3 months post‐RFA 10,11 . Similarly, studies assessing patients receiving other interventional pain modalities have identified similar outcome associations.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The results for response to RFA among age, BMI, gender, and smoking correlate with those of other studies that examined outcomes at 3 months post‐RFA 10,11 . Similarly, studies assessing patients receiving other interventional pain modalities have identified similar outcome associations.…”
Section: Resultssupporting
confidence: 75%
“…However, when examining OME units, a study by Odonkor et al found no significant difference in response to lumbar RFA for individuals on higher doses of opiates. Conversely, our study suggests improved outcomes for those on OME < 20 and a graded decrease in response as OME units are increased 11 . This association may also transcend into populations undergoing other pain procedures.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Hohenberger et al 57 pointed out that 95.1% of patients with spinal synovial cysts had experienced local and radicular pain as the predominant symptom, and 47.5% patients appeared to have preoperative sensory and motor deficits. Particularly, Odonkor et al 58 pointed out, inciting events are common in patients diagnosed with facetogenic LBP and may be associated with a positive outcome. Hughey et al 59 showed an algorithm that compares, including starting “Oswestry disability index”, pain scores, and both gender and smoking history, favorably to that of diagnostic MBB in terms of prediction accuracy, which may improve selecting patients with LFJ syndrome.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…14,67 In contrast, around half of the cases of specific spinal pain can be attributed to an inciting event, though the pathophysiological relationship between the event and etiology may be nebulous. [68][69][70] The reported incidence of space adaptation back pain in astronauts is 52% to 68%, with up to 4% experiencing severe symptoms. 14,67 The duration of space adaptation back pain generally does not exceed 12 days and has been effectively treated with oral medications, position changes (knees-to-chest), and exercise.…”
Section: Diagnosis and Treatment Considerations Of Space Adaptation B...mentioning
confidence: 99%